2020
DOI: 10.1016/j.wear.2019.203169
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and intrinsic lubricity of in situ Ti3SiC2–TiSi2–TiC MAX phase composite fabricated by reactive spark plasma sintering (SPS)

Abstract: and intrinsic lubricity of in situ Ti 3 SiC 2 -TiSi 2 -TiC MAX phase composite fabricated by reactive spark plasma sintering (SPS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…As a metalloceramic material, MAX phase has both metallic properties (having high stiffness, machinability, electrical, and thermal conductivities) and ceramic properties (with high thermal stability and oxidation resistance); [4,114,[120][121][122][123][124] these materials can be used as reinforcing agents to improve bulk and surface properties. [120,125] Using MAX Ti 3 AlC 2 , for example, the wear resistance increases, the friction coefficient decreases and that the microhardness improves up to 39.24 HV, attaining a 75.4% improvement.…”
Section: Max-based Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a metalloceramic material, MAX phase has both metallic properties (having high stiffness, machinability, electrical, and thermal conductivities) and ceramic properties (with high thermal stability and oxidation resistance); [4,114,[120][121][122][123][124] these materials can be used as reinforcing agents to improve bulk and surface properties. [120,125] Using MAX Ti 3 AlC 2 , for example, the wear resistance increases, the friction coefficient decreases and that the microhardness improves up to 39.24 HV, attaining a 75.4% improvement.…”
Section: Max-based Compositesmentioning
confidence: 99%
“…According to Figure 8, the best overall mechanical properties were observed when 20 wt% SnO 2 was used in the fabrication process; the improvements were attributed to the in situ formation of Al 2 O 3 and solid solution strengthening effects; furthermore, the SEM images revealed a creation of tribofilm attributed mostly to the tribo-oxidation reaction. [139] Using Ti, Si, and graphite powder as starting materials, Magnus et al [121] deployed a reactive spark plasma sintering approach to fabricate in situ Ti 3 SiC 2 -TiSi 2 -TiC MAX phase nanocomposite (with 80 wt% Ti 3 SiC 2 , 14 wt% TiC, and 6.0 wt% TiSi 2 ) where they focused on the poor oxidation behavior, wear resistance, grain fracture, and the pull-outs of monolithic Ti 3 SiC 2 when the intergranular TiC phase acts as reinforcement; the measured hardness value of the composite sample was ≈7.8 GPa while the theoretical value reported for monolithic Ti 3 SiC 2 is ≈4 GPa, [140] attaining 95% improvement; the main reason of tribological improvement is that the TiC phase might shield Ti 3 SiC 2 and acts as a load bearing part during wear and as a reinforcing agent at the TiC-Ti 3 SiC 2 interface. Intrinsic solid lubrication behavior of the fabricated composites was confirmed for shearing graphitic carbon as well as the frictional Figure 7.…”
Section: (10 Of 20)mentioning
confidence: 99%
“…Reprinted with permission. [ 150 ] Copyright 2020, Elsevier. e) A schematic drawing showing the synthesis of Mo 1.33 C MXene by the etching method.…”
Section: Applications Of Max Phasesmentioning
confidence: 99%
“…[ 149 ] Thus, Ti 2 AlC coating shows great potential to be used as high‐temperature tribological coating. Magnus et al [ 150 ] reported the evidence of the intrinsic lubricity of Ti 3 SiC 2 –TiSi 2 –TiC composite and proposed the wear mechanisms of the composite. As shown in Figure 18c, many chemical and physical reactions occurred during wearing, including the formation of graphitization, spallation of tribofilm, grain pull‐out and fracture, regraphitization, etc.…”
Section: Applications Of Max Phasesmentioning
confidence: 99%
See 1 more Smart Citation